“Sand Types”: A New Physicochemical Classification of Sand and Its Mapping Using Conditional Strings in ArcGIS10.x - A. C. Dinesh; N. V. Nisha; Pillai Rachna (Journal of Engineering)
The economic viability of sand in the construction industry depends on its size, shape, shell content, etc. It is imperative to understand the proportions of sand subclasses and shell content in sand sediment while planning exploration and mining. The existing sediment classifications (Particle Size Distribution Classifications) based on Sand-Silt-Clay (SSC) or Gravel-Sand-Mud (GSM) of different authors have not addressed these issues and it remains as a gap area till now. Hence, a new physicochemical classification (“Sand Types”) of sand that falls in the “sand fields” of SSC plots pertaining to two famous authors is being proposed. The freeware program “Sand Types” developed for plotting types of sand in the ternary diagram helps to plot the data in a triangular diagram and identify their physicochemical properties. The program also offers conditional strings that are prepared based on the proposed classification and are coupled with that of SSC classifications. These conditional strings work in ArcGIS10.x platform for the preparation of sediment distribution maps with meaningful information. This would enable construction industry/end-users to plan and execute detailed exploration and mining programs at great ease.